Elderly gynaecological cancer patients at risk for poor end of life care: a population-based study from the Swedish Register of Palliative Care. (2nd June 2020) - Lindemann, K.; Martinsson, L.; Kaasa, S.; Lindquist, D.
Abstract: Introduction: Poorer end-of-life (EOL) care for elderly cancer patients has been reported. We assessed the impact of age on 13 indicators for the quality of EOL care as well as adherence to 6 national quality indicators in gynaecological cancer patients. Methods: Age-dependent differences in 13 palliative care quality indicators were studied in gynaecological cancer patients registered in the population-based Swedish Register of Palliative Care. Association between the patient's age and each quality indicator was analyzed by logistic regression, adjusted for place of death where appropriate. Adherence to six national quality indicators determined by the Swedish National Board of Health and Welfare was estimated in all patients. Results: We included 3940 patients with the following age distribution: 1.6% were 18–39 years of age, 12.3% 40–59 years, 37.2% 60–74 years, 28.9% 75–84 years and 20% were ≥85 years. Age-dependent differences in implementation rate were present for some of the 13 quality indicators. Compared to elderly cancer patients, younger patients were more likely to be cared for by a specialized palliative care service, more often informed about imminent death as well as assessed for pain. For most national quality indicators, the goal level was not met. Only for the 'on demand prescription for pain', the goal level was reached. Conclusions: EOL care did not meet national quality indicators in this population-based data from Sweden, in particular in the elderly population. Elderly gynaecological cancer patients are at high risk of poorer EOL care without the involvement of specialized palliative care services. Palliative care services need to be implemented across all institutions of EOL care to ensure good and equal care.